A liposomal RNA vaccine inducing neoantigen-specific CD4+ T cells augments the antitumor activity of local radiotherapy in mice. (1st January 2020) - Salomon, Nadja; Vascotto, Fulvia; Selmi, Abderaouf; Vormehr, Mathias; Quinkhardt, Juliane; Bukur, Thomas; Schrörs, Barbara; Löewer, Martin; Diken, Mustafa; Türeci, Özlem; Sahin, Ugur; Kreiter, Sebastian
ABSTRACT: Antigen-encoding, lipoplex-formulated RNA (RNA-LPX) enables systemic delivery to lymphoid compartments and selective expression in resident antigen-presenting cells. We report here that the rejection of CT26 tumors, mediated by local radiotherapy (LRT), is further augmented in a CD8 + T cell-dependent manner by an RNA-LPX vaccine that encodes CD4 + T cell-recognized neoantigens (CD4 neoantigen vaccine). Whereas CD8 + T cells induced by LRT alone were primarily directed against the immunodominant gp70 antigen, mice treated with LRT plus the CD4 neoantigen vaccine rejected gp70-negative tumors and were protected from rechallenge with these tumors, indicating a potent poly-antigenic CD8 + T cell response and T cell memory. In the spleens of CD4 neoantigen-vaccinated mice, we found a high number of activated, poly-functional, Th1-like CD4 + T cells against ME1, the immunodominant CD4 neoantigen within the poly-neoantigen vaccine. LRT itself strongly increased CD8 + T cell numbers and clonal expansion. However, tumor infiltrates of mice treated with CD4 neoantigen vaccine/LRT, as compared to LRT alone, displayed a higher fraction of activated gp70-specific CD8 + T cells, lower PD-1/LAG-3 expression and contained ME1-specific IFNγ + CD4 + T cells capable of providing cognate help. CD4 neoantigen vaccine/LRT treatment followed by anti-CTLA-4 antibody therapy further enhanced the efficacy with complete remission of gp70-negative CT26 tumors and survival of all mice. Our data highlight the power of combining synergistic modes of action and warrants further exploration of the presented treatment schema.